STRATEGI PEMASARAN DESA WISATA BLIMBINGSARI KABUPATEN JEMBRANA - Ratu, Cristina; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 4 No 1 (2016): VOL 4, NO 1 (2016): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2016)
Abstract Village tourism is growing significantly nowadays. It is happening because the transition of mass tourism becomes alternative tourism, which village tourism is a kind of alternative tourism. But, the significant growth of village tourism still facing problem. The problem is about marketing. One of village tourism that facing marketing problem is Blimbingsari Village Tourism. The main objective of this research is to find marketing strategies for Blimbingsari Village Tourism. Data were collected through observation, literature study and interviews the tourism manager that responsible in tourism at Blimbingsari, that is tourism committee. After collecting process, the data analyzed descriptively and analyzed the marketing strategies using the SWOT approach. The result of analysis showed that strength, weakness, opportunity and threat of Blimbingasri Village Tourism could created strategies that supported the marketing of that village tourism. Based on the analysis through the SWOT approach, the strategies are SO strategy that is packaging of product, WO strategy that is promotion, ST strategy that is repositioning, and WT strategy that is giving the extra service for tourist.
Keywords: marketing strategy and village tourism